(untitled) (The Pakistan Development Review, 1985)
The less developed countries face real problems in allocating their scarce resources to multifarious needs such as the development of adequate physical and social infrastructure and for investment in the primary and secondary sectors. Thus, the role of the government in the developmental process in these countries should be to control investment in the public and private sectors with a view to maximizing both national income and social welfare. For this, it is imperative that only such projects arc selected as contribute most to the achievement of these objectives. This necessitates sound planning.